(untitled) (Proceedings OPTIMAL, 2025)
Cephalopelvic disproportion (CPD) is an abnormality of the birth canal between the large pelvic cavity and the baby’s head which causes labor to not progress. The purpose of this writing is to reduce pain levels by using slow stroke back massage techniques and peppermint aromatherapy. This scientific paper uses a case study on mother post cesarean section for indications of cephalopelvic disproportion (CPD). The location of the case study was Hermina Hospital Jatinegara on May 13-15, 2024. The results of the assessment obtained by the patient complained of pain in the operating wound on a scale of 6. Problems found acute pain, risk of infection, ineffective breastfeeding, readiness to increase knowledge of types of birth control methods and baby care at home. Nursing actions taken to manage pain by providing slow stroke back massage techniques and peppermint aromatherapy. Pain evaluation was carried out for 3 days with the use of this technique carried out 1x a day for a duration of 10-15 minutes, there was a decrease in pain from scale 6 to scale 3. Recommendations for nurses are expected that the application of nonpharmacology with slow stroke back massage and peppermint aromatherapy is effective in reducing pain so that it can be used in patients post cesarean section.